1998
DOI: 10.1143/ptp.99.713
|View full text |Cite
|
Sign up to set email alerts
|

Space-Time Structures from IIB Matrix Model

Abstract: We derive a long distance effective action for space-time coordinates from a IIB matrix model. It provides us an effective tool to study the structures of space-time. We prove the finiteness of the theory for finite $N$ to all orders of the perturbation theory. Space-time is shown to be inseparable and its dimensionality is dynamically determined. The IIB matrix model contains a mechanism to ensure the vanishing cosmological constant which does not rely on the manifest supersymmetry. We discuss possible mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
255
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(266 citation statements)
references
References 18 publications
9
255
0
2
Order By: Relevance
“…The large N behavior of this quantity has been observed to amount to R new / √ g = 3.30(1) · N 1/4 , which is consistent with the prediction based on the low-energy effective theory [18].…”
Section: Ssb Of Lorentz Symmetry ?supporting
confidence: 85%
See 1 more Smart Citation
“…The large N behavior of this quantity has been observed to amount to R new / √ g = 3.30(1) · N 1/4 , which is consistent with the prediction based on the low-energy effective theory [18].…”
Section: Ssb Of Lorentz Symmetry ?supporting
confidence: 85%
“…In the IIB matrix model, the eigenvalues of the bosonic matrices A µ are interpreted as the space-time coordinates [2,18,23]. We adopt this point of view in the 4D model as well.…”
Section: Ssb Of Lorentz Symmetry ?mentioning
confidence: 99%
“…In fact we can in principle predict the dimensionality of spacetime, the gauge group and the matter contents by solving this model. We have already initiated such investigations in [3] [4]. We refer our recent review for more detailed expositions and references [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [8], it has been shown that the effective potential for x iµ can be given by a branched-polymer like attractive interaction among N points in D-dimensional space-time represented by x iµ (i = 1, · · · , N). Now counting the power of x i in the partition function, the integration measure for x iµ gives…”
mentioning
confidence: 99%